OBLIGATORY PROGRAM AND ITS EFFICACY IN PATIENTS WITH OSTEOARTHRITIS - S S Yakushin; S. P. Filonenko; N V Minayeva; N A Rondaleva (Научно-практическая ревматология)
The aim of the research was to create education programme and investigate its effict in patients with osteoarthritis. The programme included 9 subjects, concerning of main questions of osteoarthritis self-control. The course was conducted 2 times a week during 1 months in closed osteoarthritis out-patient groups. 36 osteoarthritis out-patients were taght in 2 groups. The number of the patients in each group was 18 patients. Each study lasted 1-1,5 hours in the osteoarthritis groups. The patients were examined and questionnaired before and 6 months after intervention. The main results of the programme were sighnificant in provement of know ledge about their disease, decreasing of exacerbation in 1,5 times, visits to doctors, jointache, for 5,7 mm, on the visual analogical scale and statilization of functions of joints. The spectrum of medicine was changed to mordener and safer. There was decreasing of other effects of medicine. Thus achieved results showed the effectiveness of suggested training programme and nesessity of its using for complex treatment of osteoarthritis patients.